2017
DOI: 10.1073/pnas.1617542114
|View full text |Cite
|
Sign up to set email alerts
|

Hunter-gatherer residential mobility and the marginal value of rainforest patches

Abstract: The residential mobility patterns of modern hunter-gatherers broadly reflect local resource availability, but the proximate ecological and social forces that determine the timing of camp movements are poorly known. We tested the hypothesis that the timing of such moves maximizes foraging efficiency as huntergatherers move across the landscape. The marginal value theorem predicts when a group should depart a camp and its associated foraging area and move to another based on declining marginal return rates. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 43 publications
2
66
0
2
Order By: Relevance
“…Human hunter-gatherers are a clear example of such behaviours, and there is qualitative evidence of MVT-like behaviour in hunter-gatherer foragers (Smith et al, 1983). Furthermore, using historical foraging data from a nomadic hunter-gatherer society, Venkataraman et al (2017), showed that the 'residential mobility' of a group fits well with MVT predictions. That is, the decision of when to move camp conforms with optimal leaving times based on the local habitat and broader environment in which the group resides.…”
Section: Social Foragingmentioning
confidence: 88%
“…Human hunter-gatherers are a clear example of such behaviours, and there is qualitative evidence of MVT-like behaviour in hunter-gatherer foragers (Smith et al, 1983). Furthermore, using historical foraging data from a nomadic hunter-gatherer society, Venkataraman et al (2017), showed that the 'residential mobility' of a group fits well with MVT predictions. That is, the decision of when to move camp conforms with optimal leaving times based on the local habitat and broader environment in which the group resides.…”
Section: Social Foragingmentioning
confidence: 88%
“…The emergent hunter-gatherer pattern resulted in long delays between the acquisition and the use of tools, as well as geographical distance between the sources of raw material for tools and killing or butchering sites (Gärdenfors and Osvath, 2010). The hunter-gatherer lifestyle involved frequent shifts of camp as resources were depleted, forcing the group to move on to another more abundant region-a pattern still evident in present-day hunter-gatherers (Venkataraman et al, 2017).…”
Section: Language As Gesturementioning
confidence: 99%
“…Animal aggregations can yield some of the most striking spatial patterns in nature. They are observed in almost all taxa (Ims 1988;Sumpter 2006;Bruce and Bradford 2015;Venkataraman et al 2017), and may comprise several species (Heymann and Buchanan-Smith 2000;Goodale et al 2010). In some cases, they result directly from the existence of large-scale resource heterogeneity, but in others, animals aggregate more than what would be expected on the basis of resource distribution alone (Brown and Orians 1970;Jeanson et al 2005).…”
Section: Introductionmentioning
confidence: 99%